Effects of a Clinical Exercise Program on Health-Related Fitness and Quality of Life in Spanish Cancer Patients Receiving Adjuvant Therapy. (December 2022) - GilHerrero, Lucía; Courneya, Kerry S.; McNeely, Margaret L.; Castellanos, Mónica; González Marquez, Ana Isabel; Pollan, Marina; Casla-Barrio, Soraya
Objective: To report the feasibility and effectiveness of a newly developed clinical exercise program for improving maximal cardiorespiratory fitness in Spanish cancer patients receiving adjuvant chemotherapy or radiation. We also examined the effectiveness of the exercise program for improving maximal muscular strength, body composition, fatigue, and quality of life, and explored if the effectiveness varied based on selected patient characteristics. Design: The study was a single group implementation feasibility study using a pre-posttest design. Methods: Participants performed a 12-week, twice-weekly, supervised, multi-component exercise program during adjuvant therapy. Paired t -tests were used to assess pre-post changes, and analyses of covariance were used to compare effectiveness based on selected patient characteristics. Results: We had 100 cancer patients referred to the clinical exercise program of which 85 (85%) initiated the exercise program and 76 (89%) completed the post-intervention fitness assessment. Exercise significantly improved VO2max by 4.8 mL/kg/minutes ( P < .001, d = 0.74). Exercise also significantly improved chest strength ( P < .001, d = 0.82), leg strength ( P < .001, d = 1.27), lean body mass ( P < .001, d = 0.11), skeletal muscle mass ( P < .001; d = 0.09), fat mass ( P < .001; d = 0.10), % body fat ( P < .001; d = 0.17), quality of life ( P = .0017; d = 0.41), and fatigue ( P = .007; d = 0.46). Treatment modality, cancer type, and age affected some exercise responses, especially related to body composition changes. Conclusions: A 12-week, supervised, multi-component exercise program was effective for improving health-related fitness and quality of life in Spanish cancer patients receiving adjuvant therapy. Our results show the benefits of incorporating clinical exercise programming into the supportive care of cancer patients receiving treatments. Registration: The study protocol is registered at ClinicalTrials.gov (NCT05078216).